Magnetically modified corn cob as a new low-cost biosorbent for removal of Cu (II) and Zn (II) from wastewater (Universitas Negeri Semarang, 2020)
Wastewater containing heavy metals can potentially harm the human and living organisms and also damage the environment and ecosystem. Wastewater containing total copper (Cu) and zinc (Zn) over the normal threshold will result in Wilson's disease and digestive health, respectively. One of the most widely used methods to remove heavy metals from wastewater is adsorption. One type of adsorbent that has gained interest among researchers was biomass-based adsorbent or biosorbent. In this work, magnetic modification was used to increase the adsorption capacity of the biosorbent. Therefore, the aim of this study was to determine the effect of magnetic modification of corncobs as biosorbent on the adsorption of Cu(II) and Zn(II) heavy metals from an aqueous solution. Magnetic modification with FeCl3.7H2O on corncobs has successfully increased the adsorption capability of Zn(II) and Cu(II) from aqueous solution. The optimum modification ratios for the adsorption of Zn(II) and Cu(II) were 1:2 and 2:1. The adsorption of these both heavy metals took place at temperature of 50Â°C with the adsorbent doses of 1 g and 1.5 g for Cu(II) and Zn(II), respectively. The highest adsorption percentages for the adsorption of Zn(II) and Cu(II) were 89.3% and 89.2%, respectively. Whereas, the maximum adsorption capacities of Cu(II) and Zn(II) were 75.76 mg/g and 63.93 mg/g, respectively. The adsorption mechanism of Zn(II) and Cu(II) has followed the Freundlich isothermal adsorption model.